The use of Nasal CPap at the Charlotte Maxeke Johannesburg Academic Hospital - Jardine, Carla (My University, 2017)
Inroduction: Nasal continuous positive airway pressure (NCPAP) is well established as a treatment for hyaline membrane disease (HMD) and other respiratory diagnoses in neonates. NCPAP is an affordable intervention which results in a reduction in the number of neonatal admissions to the intensive care unit (ICU) for ventilation. At the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) we have been using NCPAP since April 2006. Objectives: The aim of this study was to review the use of early NCPAP in our hospital setting. Methods: This was a retrospective descriptive study of all neonates ≥ 750g admitted to CMJAH between 1st January 2013 and 31st July 2014 who received NCPAP within 72 hrs of birth. The characteristics and the survival of all infants who received NCPAP was described using univariate analysis. Results: The NCPAP group (481) of neonates <1500g was significantly associated with surfactant use (p<0.0005), bronchopulmonary dysplasia (BPD) (p<0.0005) and late sepsis (p<0.0005). The survival to day 7 and to discharge of infants treated with NCPAP was significantly decreased (p<0.0005). NCPAP alone (without ventilation), improved the survival to discharge (p=0.001). The survival was 95.4% in the ≥1500g infants, compared to 87.6% in the very low birth weight (VLBW) infants (1000-1499g) and 55.2% in the extremely low birth weight (ELBW) infants (750-999g). Conclusion: NCPAP is an effective intervention for HMD; it is both cost effective and easy to use in a resource limited setting and reduces the morbidity and mortality associated with ICU admission.
This research report is submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the Department of Paediatrics and Child Health, Faculty of Health Sciences, University of Witwatersrand, Johannesburg April 2015.
Keywords: Continuous Positive Airway Pressure; Intensive Care Units; Hyaline Membrane Disease; Infant, Newborn (Neonates)